2017
DOI: 10.3390/tropicalmed2020015
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Practices Ineffective at Prevention of Plasmodium falciparum Malaria during Pregnancy in a Sub-Saharan Africa Region, Nigeria

Abstract: Pregnancy-associated malaria (PAM) is a major public health concern constituting a serious risk to the pregnant woman, her foetus, and newborn. Management of cases and prevention rely partly on effective and efficient antenatal services. This study examined the effectiveness of antenatal service provision in a major district hospital in sub-Saharan Africa at preventing PAM. A cross-sectional hospital based study design aided by questionnaire was used. Malaria diagnosis was by microscopy. Overall prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Provision of ITNs during ANC is needed in some areas. Also reviews of aspects of counselling and sensitizations during ANC to incorporate malaria preventive strategies may be needed in some settings as was the case in our study at District Hospital, Ogrute, Enugu State, Nigeria [72]. At that hospital, not only was there need for provision of ITNs, there was need for sensitization on benefits of ITNs usage.…”
Section: Current Challenges To Pam Prevention and Managementmentioning
confidence: 75%
See 4 more Smart Citations
“…Provision of ITNs during ANC is needed in some areas. Also reviews of aspects of counselling and sensitizations during ANC to incorporate malaria preventive strategies may be needed in some settings as was the case in our study at District Hospital, Ogrute, Enugu State, Nigeria [72]. At that hospital, not only was there need for provision of ITNs, there was need for sensitization on benefits of ITNs usage.…”
Section: Current Challenges To Pam Prevention and Managementmentioning
confidence: 75%
“…ITNs usage, IPTp and effective management of malarial cases) to prevention and management of PAM recommended by WHO [71] is greatly dependent on antenatal care provision for effective delivery. Though ITNs distribution, acquisition and usage by pregnant women can happen without interference from antenatal service providers, studies have indicated needs for counselling on ITNs ownership and usage [72]. Promotion of ITNs usage among pregnant women taking together with the other two antenatal care-rooted recommendations during antenatal may be more cost effective than otherwise.…”
Section: Current Challenges To Pam Prevention and Managementmentioning
confidence: 99%
See 3 more Smart Citations